Z-Number-Based Linear Programming - Aliev, R. A.; Alizadeh, A. V.; Huseynov, O. H.; Jabbarova, K. I. (International journal of intelligent systems, 2015)
Linear programming (LP) is the operations research technique frequently used in the fields of science, economics, business, management science, and engineering. Although it is investigated and applied for more than six decades, and LP models with different level of generalization of information about parameters including models with interval, fuzzy, generalized fuzzy, and random numbers are considered, until now there is no approach to account for reliability of information within the framework of LP. Professor L. Zadeh introduced the concept of a Z‐number to describe uncertain information, which is a more generalized notion closely related to reliability. The use of Z‐information is more adequate and intuitively meaningful for formalizing information structure of a decision problem. In this paper, we suggest a study of fully Z‐number based LP (Z‐LP) model to better fit real‐world problems within the framework of LP. We propose the method to solve Z‐LP problems, which utilize differential evolution optimization and Z‐number arithmetic developed by the authors. The suggested model and solution method for Z‐LP are illustrated on the basis of a benchmark LP problem, where we conduct comparative analysis, which shows validity of the approach.